Empowering Students with Learning Disabilites in the Canadian Postsecondary Educational System - Stewart, Donald; Cornish, Peter; Somers, Kent (Canadian Journal of Counselling and Psychotherapy, 2007)
Large numbers of students with learning disabilities (LD) are now seeking postsecondary education in Canada. Many of these students are not prepared for the personal and academic challenges associated with higher education because their disability self-awareness level and self-advocacy skills have not been adequately developed. This article describes some of the problems confronting students with LD at Canadian postsecondary institutions today and presents options that counsellors, educators, and other professionals might consider to better prepare students with LD for success. Issues related to early identification and acknowledgement of LD are emphasized as ways of empowering students with LD to develop the personal tools necessary for success in the postsecondary environment.